SUCNR1 regulates insulin secretion and glucose elevates the succinate response in people with prediabetes - Joan Sabadell‐Basallote; Brenno Astiarraga; Carlos Castaño; Miriam Ejarque; Maria Repollés-de-Dalmau; Iván Quesada; Jordi Blanco; Catalina Núñez‐Roa; M‐Mar Rodríguez‐Peña; Laia Martínez; Dario F. De Jesus; Laura Marroquí; et al. (2024)
Pancreatic β-cell dysfunction is a key feature of type 2 diabetes, and novel regulators of insulin secretion are desirable. Here we report that the succinate receptor (SUCNR1) is expressed in β-cells and is up-regulated in hyperglycemic states in mice and humans. We found that succinate acts as a hormone-like metabolite and stimulates insulin secretion via a SUCNR1-Gq-PKC-dependent mechanism in human β-cells. Mice with β-cell-specific Sucnr1 deficiency exhibit impaired glucose tolerance and insulin secretion on a high-fat diet, indicating that SUCNR1 is essential for preserving insulin secretion in diet-induced insulin resistance. Patients with impaired glucose tolerance show an enhanced nutritional-related succinate response, which correlates with the potentiation of insulin secretion during intravenous glucose administration. These data demonstrate that the succinate/SUCNR1 axis is activated by high glucose and identify a GPCR-mediated amplifying pathway for insulin secretion relevant to the hyperinsulinemia of prediabetic states.